Evaluating abiotic and microbial factors on carbonate precipitation in Lake Acigöl, a hypersaline lake in Southwestern Turkey - Balci, Nurgul; Demirel, Cansu; Akcer Ön, Sena; Gültekin, A. Haydar; Kurt, Mehmet Ali (Elsevier BV, 2018)
Abstract The recent carbonate precipitation occurs in Lake Acigol, a hypersaline playa lake. Elucidating precipitation mechanisms of carbonate minerals under particularly supersaturated ionic solution at low temperature may hold key understanding to recognize microbial fingerprints throughout the Earth history. In the presented study abiotic and microbial factors controlling carbonate precipitation mechanisms are investigated by using geochemical, isotopic and chemical approaches. Our data demonstrated that aragonite, calcite and dolomite are readily precipitated in oxic column of lake water in decreasing order. Major metabolites profile of pore water showed that carbonate alkalinity and pH increased by microbial activity seems to be insignificant in the lake sediments to support precipitation. On the contrary a positive correlation between δ13C and δ18O values of carbonates suggest that carbonate super-saturation occurs as a result of evaporation and associated degassing of CO2in the lake basin. However, a putative microbial role such as binding of cations to microbial cell wall or EPS to overcome kinetic inhibitors (e.g Mg2+) is likely possible in the lake as a driving carbonate precipitation mechanism. Overall, the present study demonstrated that carbonate precipitation in the lake is the result of complex players, such as lake water chemistry, ionic interactions, evaporation and EPS-organic compounds (e.g EPS) in addition to kinetic microbial processes. The data also provide a fundamental insight which is that revealing of changes in carbonate mineralogy of the lake, strongly influenced by evaporation, would provide significant insights about paleoclimatic conditions of the region.